Tailored Local Bandgap Modulation as a Strategy to Maximize Luminescence Yields in Mixed‐Halide Perovskites. Issue 18 (12th June 2021) - Feldmann, Sascha; Neumann, Timo; Ciesielski, Richard; Friend, Richard H.; Hartschuh, Achim; Deschler, Felix
Abstract: Halide perovskites have emerged as high‐performance semiconductors for efficient optoelectronic devices, not least because of their bandgap tunability using mixtures of different halide ions. Here, temperature‐dependent photoluminescence microscopy with computational modelling is combined to quantify the impact of local bandgap variations from disordered halide distributions on the global photoluminescence yield in mixed‐halide perovskite films. It is found that fabrication temperature, surface energy, and charge recombination constants are keys for describing local bandgap variations and charge carrier funneling processes that control the photoluminescence quantum efficiency. It is reported that further luminescence efficiency gains are possible through tailored bandgap modulation, even for materials that have already demonstrated high luminescence yields. The work provides a novel strategy and fabrication guidelines for further improvement of halide perovskite performance in light‐emitting and photovoltaic applications. Abstract : Halide perovskite films show remarkable optoelectronic performance although their fabrication from solution should introduce harmful energetic disorder. The authors now quantify regimes where local charge accumulation at energy minima can indeed be beneficial for the luminescence yields, and identify key fabrication factors for their optimization.